Pelatihan Pembuatan Siniar Pembelajaran Bagi Guru-Guru Sekolah Menengah Kejuruan - Asep Soegiarto; Abdul Kholik (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
In this article, we are introducing a new community engagement initiative that aims to train vocational school teachers in creating impactful learning podcasts. The goal of this training is to equip educators with the necessary skills to develop dynamic audio content that combines visual and textual elements, resulting in interactive learning experiences. Throughout the program, participants will explore scriptwriting, recording techniques, and post-production editing, all while learning how to effectively integrate multimedia components to enhance student engagement and comprehension. By offering practical exercises and expert feedback, this initiative empowers educators to adapt their teaching methods to the digital age, ultimately enhancing the quality of vocational education. This training bridges the gap between traditional teaching methods and modern learning preferences, and promotes an enriched educational environment while nurturing the growth of educators as innovative pedagogical influencers.